Are pyroxasulfone and pyroxasulfone plus flumioxazin options for application in transplanted onions? - Bordignon, Laura (2024)
This study aimed to evaluate the efficiency and selectivity of the herbicides pyroxasulfone and pyroxasulfone plus flumioxazin for transplanted onion, which currently do not have registration for this crop in Brazil. The experiment was conducted in two commercial crops in Imbuia and Curitibanos, SC, Brazil, with four replications. The herbicides application was carried out pre-emergence of weeds, after onion transplanting in both experiments. The Imbuia experiment had eight treatments: T1: diuron (D) + pyroxasulfone (PYR) (500 + 50 g ha-1), T2: D + PYR (500 + 75 g ha-1), T3: D + PYR (500 + 100 g ha-1), T4: D + PYR + flumioxazin (FLU) [500 + (60 + 40 g ha-1)], T5: D + PYR + FLU [500 + (75 + 50 g ha-1)], T6: D + PYR + FLU [500 + (90 + 60 g ha-1)], T7: Weed free check, and T8: Control. In Curitibanos, had an additional treatment, with application of diuron (500 g ha-1). Evaluation consisted of identification and weed control, crop phytotoxicity, onion stand, and diameter and yield of bulbs. Pyroxasulfone and pyroxasulfone plus flumioxazin, with diuron, were effective in control of Polygonum persicaria, Galinsoga parviflora, and Coronopus didymus, regardless of the dose used. Diuron with pyroxasulfone at a dose of 100 g ha-1 and with pyroxasulfone plus flumioxazin (60 + 40.75 + 50, and 90 + 60 g ha-1) were effective in Raphanus spp. control in boths experiments. The control showed losses in its total yield compared to the weed free check, decreasing by 81.7% in Imbuia and 90,3% in Curitibanos. The herbicides used were selective and are importante tools for weed management in transplanted onion.